Paired electrochemical C-H bromination of (hetero)arenes with 2-bromoethan-1-ol - Lv, Yanxia; Hou, Zhong-Wei; Li, Pinhua; Wang, Lei (ORGANIC CHEMISTRY FRONTIERS, 2023)
A site-selective electrochemical C-H bromination of (hetero)arenes with 2-bromoethan-1-ol through paired electrolysis has been developed. The C-H bromination reactions depend on the anodic oxidation of Br- produced by the cathodic reduction of 2-bromoethan-1-ol with available ethylene oxide and hydrogen evolution. The method has good compatibility with common functional groups and the scale-up electrolysis can easily be performed. A wide variety of brominated products were obtained with satisfactory yields at room temperature in a simple undivided cell.